A Open Label Clinical Study – To Ascertain The Effect Of Homoeopathic Medicines In Cases Of Psycho-Somatic Disorder With Miasmatic Approach - Srivastava, Sanjeev Kumar; Kumar, Sunil (Journal of Neonatal Surgery, 2025)
Background: Psychosomatic illnesses challenge this paradigm because they present physically, but are thought to have, at least in part, a psychological origin.Psychosomatic disorder, also called psycho physiologic disorder, is a condition in which psychological stresses adversely affect physiological (somatic) functioning to the point of distress. Aim: To ascertain the effectiveness of homoeopathic remedies in cases of Psycho-somatic disorder. Objective: 1. To measure changes in symptom severity, quality of life and overall well-being. 2. To assess of psychological factors in cases of Psycho-somatic disorder. 3. To assess the miasmatic background in the cases of Psycho-somatic disorder. Methods & Results: A prospective single-arm clinical trial involved 100 patients suffering from Psychosomatic disorder at OPD of B R V Homoeo Clinic And Research Unit Prayagraj. Psychosomatic Symptom Scale (PSSS) is a questionnaire used to assess psychosomatic symptoms with score was utilized to gauge improvement. The average score before treatment (2.78) decreased to (1.54) after treatment, resulting in a mean difference of 1.24. The calculated t-value (13.77) was greater than the critical value (0.78) at a 5% significance level (p < 0.000is 01), indicating a highly significant enhancement. Conclusion: Customized homoeopathic treatments led to a statistically significant reduction in psychosomatic disorder and associated symptoms. The findings indicate that homoeopathy presents a safe, effective, and non-invasive option for addressing psychosomatic disorder. Keywords: psychosomatic disorder, Psychosomatic Symptom Scale (PSSS) Homoeopathy, Constitutional Treatment, Single Arm Clinical Trial, Miasmatic Analysis, Symptom Score, Clinical Improvement. Aim: To ascertain the effectiveness of homoeopathic remedies in cases of Psycho-somatic disorder